An Experimental Investigation of Karanja Biodiesel Production in Sarawak, Malaysia - Harreh, Dewi; Saleh, Aa A.; Reddy, A. N.R.; Hamdan, Sinin (Hindawi Limited, 2018)
The application of nonedible feedstock for the production of biodiesel has become an area of research interest among clean energy experts in the past few years. This research is aimed at the utilization of Pongamia pinnata (karanja), a nonedible feedstock from the state of Sarawak, Malaysia, to produce biodiesel to be known as crude karanja oil (CKO). A one-step transesterification process utilizing 7: 1-10: 1 wt% methanol (CH3OH) and 0.5-1.2 wt% sodium hydroxide (NaOH) at 65°C for 1.5 hrs has been used for the biodiesel production yielding 84% conversion. The physiochemical properties of the CKO produced revealed that it conforms with EN14214 standards for brake power (BP), brake specific fuel consumption (BSFC), and brake thermal efficiency (BTE) as they are all noted be optimal at B40. © 2018 Dewi Harreh et al.